Multidimensional comparison of life cycle footprint of hydrogen production technologies - Péter Németh; Anikó Zseni; András Torma (Cleaner Engineering and Technology)
Hydrogen as an energy carrier will play an important role in the future in achieving sustainable development goals in the energy and mobility sectors as well as to reach decarbonization goals. Currently adopted hydrogen strategies foresee a significant increase in the amount of hydrogen used in the future. To meet this increased volume in the most sustainable way, a careful analysis of potential hydrogen production technologies is necessary, considering real environmental impacts. This paper provides a comprehensive overview of different non-renewable and renewable hydrogen production technologies and evaluates their environmental effects based on global warming potential (GWP). Environmental footprint data discussed in this paper are based on published life-cycle assessment (LCA) results. As direct comparison of LCA results is difficult due to different LCA scenarios, selected system boundaries, various material components and manufacturing techniques, a novel multidimensional comparison approach was developed to understand LCA results better and to give a more comprehensive picture of environmental footprint components. In addition to methodological issues, the key influencing factors of the carbon footprint of different hydrogen production technologies were also identified. It is not possible to identify one stand-alone technology that would be the most environmentally friendly in all circumstances, it is essential to investigate all the technologies in the given context of use. Regarding water-splitting, it is outstandingly crucial to examine the source of the electricity because it strongly influences the GWP of this H2 production technology. If the GWP of the electricity is high, this technology could be more harmful to the environment than the steam methane reforming (SMR).